1985
DOI: 10.1364/josaa.2.000350
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the relative three-dimensional positions of two moving points

Abstract: We show that four orthographic projections of two rigidly linked points are compatible with at most four interpretations of the relative three-dimensional positions of the points if the points rotate about a fixed axis--even when the points as a system undergo arbitrary rigid translations. A fifth view (projection) yields a unique interpretation and makes zero the probability that randomly chosen image points will receive a three-dimensional interpretation. Assuming that the points rotate at a constant angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 2 publications
1
33
0
Order By: Relevance
“…(4) Are two views sufficient for accurate detections of surface curvature, as suggested by Droulez and Comilleau-Peres (1990), Koenderink and van Doom (1991), and Todd and Bressan (1990)? Most alternative computational models (e.g., Hoffman & Bennett, 1985, 1986Ullman, 1979) need three "distinct" views to recover the 3-D structure of a moving object.…”
Section: mentioning
confidence: 99%
“…(4) Are two views sufficient for accurate detections of surface curvature, as suggested by Droulez and Comilleau-Peres (1990), Koenderink and van Doom (1991), and Todd and Bressan (1990)? Most alternative computational models (e.g., Hoffman & Bennett, 1985, 1986Ullman, 1979) need three "distinct" views to recover the 3-D structure of a moving object.…”
Section: mentioning
confidence: 99%
“…Examples of algorithms that derive a 3D configuration from a set of n points (or similar features) displayed in each of m frames are Hoffman and Bennett (1985) and Ullman (1979Ullman ( , 1985, or see Braunstein, Hoffman, Shapiro, Andersen and Bennett (1987) for a more empirical treatment. A list of visual features is identified and located in 2D space on each frame.…”
Section: Feature -~Orre~~onde~~e Modelsmentioning
confidence: 99%
“…It is interesting to contrast this with a manipulation which eliminates the ability to track individual image features (dots) over multiple frames. Models that emphasize the extraction of specific image features and their image plane location (Hoffman & Bennett, 1985;Ullman, 1979Ullman, , 1985 might predict that eliminating feature stability should have an equally large impact on the shape identification. We investigated this hypothesis by comparing feature stability over a full 30 frame image sequence with stimuli in which features (surface dots) were stable for only 3 and 2 frames, after which they were replaced with a different random sample of dots (Fig.…”
Section: Equated Intensity Control (Experiments 2)mentioning
confidence: 99%
“…One way to recover the structure and motion of corresponding points is from discrete views of the points. Using the assumption of rigid, fixed-axis rotation Hoffman and Bennett (1985) showed that it is possible to recover the structure and motion of two points given five discrete views. Thus, when five views of two corresponding points exist, both the axis of rotation and the angular velocity can be obtained from the profile sequence.…”
Section: Recovering the Global Properties Of Motionmentioning
confidence: 99%
“…Much current research has concentrated on the recovery of shape under the assumption that the shape-recovery algorithm is provided with the motion of identifiable points (the correspondence problem is solved). Some of these theories state the minimal conditions which are necessary to recover a unique structure from general 3-D rigid motion (Huang and Lee, 1989;Longuet-Higgins & Prazdny, 1980;Ullman, 1979) or more constrained motion (Hoffman & Bennett, 1985Hoffman & Flinchbaugh, 1982;Longuet-Higgins, 1982;Webb & Aggarwal, 1981). Other theories describe how the instantaneous 2-D motion limits, but does not uniquely specify, the possible 3-D interpretations (Koenderink & van Doorn 1975, Todd & Bressan, 1990Ullman, 1983) or similarly how 2 discrete views limit the possible interpretations of 3-D shape (Bennett, Hoffman, Nicola & Prakash, 1989;Huang & Lee, 1989, Koenderink & van direction just grazes an object's surface (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%